Analysis of English Learning Needs for Travel Bureau Students in Bali, Indonesia - Ayu Sulasmini, Ni Made; I Nengah Sudipa; I Wayan Simpen; Made Sri Satyawati (Enigma Institute, 2024)
The tourism industry in Indonesia, especially Bali, has developed rapidly in recent years. This drives the need for skilled workers in the tourism sector, including good English language skills. This research aims to analyze the English language learning needs of students majoring in Travel Bureaus in Bali, Indonesia. This research uses quantitative and qualitative methods. Data was collected through a survey of 100 students majoring in Travel Bureau and in-depth interviews with 10 lecturers and 5 tourism industry practitioners. The research results show that students majoring in Travel Bureau have a high need to improve their English language skills, especially in the aspects of speaking, listening, and reading. This need is driven by the demands of work in the tourism industry, where English is widely used to communicate with foreign tourists. This research provides an overview of the English language learning needs for students majoring in Travel Bureaus in Bali, Indonesia. The findings of this research can be used to develop English language learning programs that are more effective and relevant to the needs of the tourism industry.